The alarmin Mrp8/14 as regulator of the adaptive immune response during allergic contact dermatitis. (27th November 2012) - Petersen, Beatrix; Wolf, Marc; Austermann, Judith; van Lent, Peter; Foell, Dirk; Ahlmann, Martina; Kupas, Verena; Loser, Karin; Sorg, Clemens; Roth, Johannes; Vogl, Thomas
Abstract : Mrp8 and Mrp14 are endogenous alarmins amplifying inflammation via Toll‐like receptor‐4 (TLR‐4) activation. Due to their pro‐inflammatory properties, alarmins are supposed to enhance adaptive immunity via activation of dendritic cells (DCs). In contrast, analysing a model of allergic contact dermatitis (ACD) we observed a more severe disease outcome in Mrp8/14‐deficient compared to wild‐type mice. This unexpected phenotype was associated with an enhanced T‐cell response due to an accelerated maturation of DCs in Mrp8/14‐deficient mice. Accordingly, Mrp8, the active component of the heterocomplex, inhibits early DC maturation and antigen presentation in a TLR‐4‐dependent manner. Transfer of DCs purified from the local lymph nodes of sensitized Mrp8/14‐deficient to wild‐type mice determined the outcome of ACD. Our results link a pro‐inflammatory role of the endogenous TLR‐4 ligand Mrp8/14 to a regulatory function in adaptive immunity, which shows some similarities with the 'hygiene hypothesis' regarding continuous TLR‐4 stimulation and decreased risk of allergy. The alarmin Mrp8/14 as regulator of the adaptive immune response during allergic contact dermatitis: Mrp8/14, an amplifier of innate immune responses, has distinct roles in the adaptive immune system, preventing its hyper‐activation by regulating dendritic cell maturation and antigen presentation.